Hubungan Kunjungan Anc Dengan Tingkat Pengetahuan Ibu Hamil Trimester III Tentang Persiapan Persalinan Dan Kegawatdaruratan Di Puskesmas Tarakan, Kecamatan Wajo, Kota Makassar - Andi Hasnah; Suriani Tahir (Jurnal Rumpun Ilmu Kesehatan, 2022)
Anxiety in the face of labor cannot be separated from the knowledge and readiness of the mother before delivery. Mothers who have good knowledge and readiness about childbirth will take care of their pregnancy and prepare whatever is needed to face childbirth, so as to minimize maternal anxiety before delivery. Anxiety arising from lack of knowledge, such as information about pregnancy and childbirth, will have an impact on maternal unpreparedness, and will trigger a high rate of pathological pregnancies and increase the number of maternal and child deaths. (Rohani et al, 2013).